Teaching strategies for street children : a case study (school for street children Depok, West Java, Indonesia) - Kamalia, Angi Hana Sya'bani (Kulliyyah of Education, International Islamic University Malaysia, 2014)
Volunteer teachers need specific skills in teaching and handling street children because teaching street children is different from teaching students in public schools. Street children have also different social and family backgrounds. Thus, the main purpose of this study is to explore the experience of volunteer teachers, who have been teaching at an informal school set up for street children in Depok, Indonesia. Specifically this study seeks to investigate the teaching strategies employed based on teachers' experiences, the challenges faced by teachers and suggestions to improve teaching and learning. The data was collected using semi-structured interviews of four volunteer teachers, observation report and volunteer teachers' diaries. The findings revealed that questioning strategies, cooperative learning strategies, grouping, and inductive teaching strategies were the most frequently employed by teachers. Among the challenges encountered by the teachers included the students' manners and behavior and lack of parent's education. The future researchers may involve teachers and street children from different regions such as Jakarta, Bogor, Tanggerang, Bekasi, Indonesia. A comparative study between informal school for street children and formal schools, public or private has been suggested for future studies.